The Single-Molecule Long-Read Sequencing of Intestine After Soy Meal-Induced Enteritis in Juvenile Pearl Gentian Grouper, Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂ - Zhang, Wei; Tan, Beiping; Deng, Junming; Dong, Xiaohui; Yang, Qihui; Chi, Shuyan; Liu, Hongyu; Zhang, Shuang; Xie, Shiwei; Zhang, Haitao (Frontiers in Marine Science, 2021)
Intestinal inflammatory disease induced by excessive soy proteins substitution for fish meal (FM) protein is a common phenomenon. Pearl gentian grouper, Epinephelus fuscoguttatus ♀× E. lanceolatus ♂, a kind of marine fish with important economical and nutritional value, exhibited the similar problem. As far as we know, there are no reports on the full-length transcriptome of pearl gentian grouper. At present study, a library composed of 7 different treated distal intestine tissues including FM control group, 20% soybean meal substituted for fish meal (SBM20), SBM40, 20% soybean protein concentrate (SPC20), SPC40, 20% fermented soybean meal substituted for fish meal (FSBM20) and FSBM40 was constructed and sequenced using PacBio SMRT and RNA-Seq sequencing technology. As a whole, this study obtained 420006 full-length non-chimeric reads. After error correction, sequence clustering and redundancy, 82351 transcripts with high quality were obtained. In addition, a total of 77815 transcripts were annotated in seven databases (Nr, Nt, Pfam, KOG, GO, Swiss-Prot and KEGG database). Also, there were 49093 long non-coding RNAs (LncRNAs) and 141702 simple sequence repeats (SSRs) were identified, respectively. Based on the full-length transcriptome sequencing, present study found that TLR-NF-κB signaling pathway play an important role in the development of SBM and FSBM induced enteritis; SPC induced enteritis is mainly accompanied by a general imbalance of nutrition absorption related signaling pathways, which only affects a small part of immune related signaling pathways. This study supplies new and valuable reference transcripts, which would better facilitate further research of pearl gentian grouper.